G76(P) Management of hypertonia in children and young people (CAYP) with intrathecal baclofen (ITB) in a tertiary centre. (25th October 2020) - Chandrasegaran, D; Perides, S; Barkey, S; Lumsden, DE; Bassi, S; Lin, JP; Kaminska, M
Abstract : Aims: To review the indications for and outcomes following ITB for CAYP managed at our centre. Methods: 42 Patients undergoing ITB pump insertion from 2006 to 2015 were identified at our centre. 35 had reports available and were included in a retrospective note review, using a standardised data collection proforma. Results: Median age at ITB pump insertion was 9 (range 4 to 18). Hypertonia was described as dystonia, spasticity and/or dyskinesia. 1 Median length of follow up was 3 years. Pre-surgery goals determined the choice of outcome measures. Care Provider Child Health Index Living with Disability (CPCHILD) data, available for 23 CAYP at baseline and 18 CAYP at 1 year, improved from a median score of 45.5 to 58.2 (P=0.03, Wilcoxon signed rank test). Burke-Fahn-Marsden Dystonia Rating Scale (BFMDRS) data was available for 12 CAYP with dystonia at baseline (median 92.5 for motor, 30 for disability) and 10 CAYP at 1 year (median 98.25 for motor, median 28 for disability). Gross Motor Function Measure (GMFM) score was available for 9 CAYP at baseline (median 40), 8 CAYP at 1 year (median 47) and 7 CAYP beyond 1 year (median 43.1). Changes in GMFM and BFMDRS did not reach statistical significance. Pain was measured with paediatric pain profile, classified into most troublesome pain (MT) and pain on a good day (GD), available for 14 CAYP at baseline and 6 CAYP at 1 year. There was marked improvement in median MT pain (29 at baseline to 17 at 1 year) but less significant improvement in median GD pain (16 at baseline to 13.5 at 1 year). Conclusions: For a heterogenous cohort of CAYP with motor disorders, ITB appeared to improve ease of care and comfort as indicated by change in CPCHILD score. Multiple measures are required to fully capture benefits seen in this cohort, which should be focused on their individual needs for intervention.